Expression and Clinical Significance of MKI67 in Pancreatic Cancer - WANG Hu; YIN Yanmei; DU Haoxuan; CHEN Hao; MA Xiaopeng; DAI Aibin; ZHU Kexiang (Zhongliu Fangzhi Yanjiu, 2024)
Objectives To explore the expression, biological function, and mechanism of MKI67 in pancreatic cancer and its clinical significance. Methods The expression level, diagnosis, and prognostic value of MKI67 in pancreatic cancer were analyzed using public databases. We also investigated the association between the MKI67 with immune cell infiltration and immune checkpoint molecules. We analyzed the functional pathway enrichment to uncover the possible molecular mechanisms. qRT-PCR and Western blot assay were used to verify the expression of MKI67 mRNA and protein. Immunohistochemistry staining was used to detect the expression of MKI67 in tissue protein. Results The high expression of MKI67 was significantly associated with high histological grades and poor outcomes in pancreatic cancer. High MKI67 expression was correlated with poor prognosis of pancreatic cancer patients (P=0.009). MKI67 was an independent risk factor for the patient outcome (95%CI: 1.084-1.743, P<0.05). The MKI67 expression was positively correlated with the helper T cell 2 levels but negatively correlated with plasmacytoid DC, NK cells, mast cells, the T follicular helper, immune DC, and CD8 T cells. Conclusion MKI67 may serve as a biomarker for the diagnosis and prognosis of pancreatic cancer and the mechanism might be associated with immune escape or immunosuppression.